Выбор анализируемых характеристик при аутентификации пользователей компьютерных систем по рукописному почерку на разных этапах развития вычислительной техники - Высоцкая, Е.А. (Моделювання та інформаційні технології, 2010)
In this article the stages of development of systems of authentification
on hand-written handwriting are analysed. The parameters which are possible
and expedient for analyzing at recognition, at various stages of development are
determined. The principle of a choice most significant of points of the images of
symbols of the password, whose characteristics are analyzed at recognition, is
submitted.